Performance Testing of the Water Level Monitoring System at Internet of Things-Based Water Gates - Feby Nopriandy; Suhendra Suhendra; Leo Dedy Anjiu; Budi Setiawan (Universitas Muhammadiyah Metro, 2026)
The main problem in agricultural water management was the imbalance in water availability caused by suboptimal irrigation systems. Efforts have been made to develop a water level monitoring system that integrates ultrasonic sensors, Internet of Things (IoT) technology, and solar power to monitor irrigation automatically and in real time, especially in locations without electricity. Therefore, this study aimed to design, construction, and test the accuracy and error rates of an Internet of Things (IoT)-based water level monitoring system. The system was designed using ultrasonic sensors, the Blynk platform, an ESP32 microcontroller, and a 50 WP solar panel as the power source. Field testing was conducted on an open water channel with a depth of approximately 1.22 m. Data were collected every 5 cm within a water level range of 5–75 cm. The sensor was operated at distances ranging from 2.27 to 2.97 m. Observations were made by comparing the ultrasonic sensor’s measurements with manual measurements used as reference points. The test results show that this system has an average accuracy of 95.85%, with an average absolute measurement error of 4.15% and a calculated RMSE of 1.1412 cm. Keywords: internet of things, monitoring, ultrasonic sensor, water level